2021
DOI: 10.1128/aac.01019-21
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Meropenem and Human Serum Albumin on Expression of Carbapenem Resistance Genes and Natural Competence in Acinetobacter baumannii

Abstract: Acinetobacter baumannii A118, a mostly susceptible strain and AB5075, carbapenem-resistant, were cultured in Lysogeny broth (LB) or LB with different supplements: 3.5% human serum albumin (HSA), human serum (HS), meropenem, or meropenem plus 3.5% HSA. Natural transformation levels were enhanced in A. baumannii A118 and AB5075 cultured in medium supplemented with 3.5% HSA. Addition of meropenem plus 3.5% HSA caused synergistic enhancement of natural transformation in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…We previously observed that genes associated with β-lactam resistance, such as bla OXA-51-like , bla OXA-23 , pbp1, and pbp3, were up-regulated in A. baumannii AB5075, AMA16, and AB0057 when cultured in the presence of 3.5% HSA (51,52). To further examine if changes in genes associated with β-lactam resistance were affected by HS or HPF in the CRAB strains, qRT-PCR was used to assess the gene expression of bla OXA-51-like , bla OXA-23 , bla NDM-1 , pbp1, pbp3, and carO in cultures of the strains AMA16 and AB0057 containing HS or HPF.…”
Section: Modulation Of the Expression Of β-Lactam Resistance Genes By...mentioning
confidence: 98%
See 2 more Smart Citations
“…We previously observed that genes associated with β-lactam resistance, such as bla OXA-51-like , bla OXA-23 , pbp1, and pbp3, were up-regulated in A. baumannii AB5075, AMA16, and AB0057 when cultured in the presence of 3.5% HSA (51,52). To further examine if changes in genes associated with β-lactam resistance were affected by HS or HPF in the CRAB strains, qRT-PCR was used to assess the gene expression of bla OXA-51-like , bla OXA-23 , bla NDM-1 , pbp1, pbp3, and carO in cultures of the strains AMA16 and AB0057 containing HS or HPF.…”
Section: Modulation Of the Expression Of β-Lactam Resistance Genes By...mentioning
confidence: 98%
“…baumannii senses components of human fluids and responds by modifying its transcriptional and phenotypic profiles [46][47][48][49][50]. Human serum albumin (HSA), as well as human pleural fluid (HPF), modulates the expression of genes associated with iron uptake systems, biofilm formation, antibiotic resistance, and DNA acquisition, among others [47,51,52]. In previous studies, we observed that CRAB AB5075 genes associated with iron uptake systems were down-regulated when exposed to HPF and 0.2% HSA [47], while genes associated with β-lactam resistance were up-regulated in the presence of physiological concentrations of HSA and human serum (HS) [51,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural transformation assays were performed as were previously described [25,26]. Briefly, 20 ul of A. baumannii cells grown overnight in LB medium at 37ºC were mixed with 1 μg of pMBLe-OA-ArK (apramycin resistance) plasmid and the mixture was spotted onto twitching motility plates (10).…”
Section: Natural Transformation Assaysmentioning
confidence: 99%
“…A. baumannii transformation frequency increases in the presence of human pleural fluid and human serum albumin [13,20,25]. Furthermore, A. baumannii DNA uptake by A. baumannii occurs while moving across wet surfaces [12].…”
Section: Introductionmentioning
confidence: 99%